Design and experimental test of runner blade for small axial pico-propeller turbines model - Pribadyo Pribadyo (Politeknik Negeri Lhokseumawe, 2022)
Environmental degradation due to the use of conventional fossil fuel remains an obstacle to sustainable development. For this reason, many countries currently consider the integration of renewable energy sources into their power sectors as an economically friendly and promising alternative to the use of fossil fuels. One form of green technology is the pico-propeller turbines. This turbine works based on the pressure of flowing water and its best performance is determined by the hydraulic stability of its blades. It is thus necessary to design suitable and hydraulically stable runner blades for these turbines. Therefore, this study aims to design a suitable runner blade for a pico-propeller turbine model that will aid in the optimal extraction of electrical energy from the fluid flow in sewer lines. The turbine wheel consists of four blades per section with a diameter of 0.150 meters and a pivot point of 0.30 meters and it was designed to fit a 5-inch diameter pipe with blade angle configurations of 25°, 30°, and 35°. Furthermore, performance tests were conducted at different flow rates, ranging from 0.00134 m3/s to 0.0047 m3/s with a 3.5 m head, after which the findings were compared to that of the other research. The results showed that maximum efficiency and performance were achieved with the blade angle of 25° at a flow rate of 0.0027 m3/s.